Generation Z needs resources and media for marine biology learning based on local potential - Sam, Nur Fitriana; Retnaningati, Dewi; Munira, Munira (JPBIO (Jurnal Pendidikan Biologi), 2025)
A needs analysis required to be done before developing a product. This research aims to analyze the need for learning resources and learning media in marine biology courses based on local potential from the perspective of students who are Generation Z. The respondents in this research were 87 students. Questionnaires are distributed via Google Forms. Data is presented quantitatively by looking at the percentage of answers from respondents. According to students, learning resources and teaching materials based on local potential need to be developed. To suit Generation Z, the recommended learning resources and learning media are digital-based and have challenging activities.